Organizational internal environment, role clarity and citizenship behavior at casualty emergency centers - Henry, Kibedi; Julius, Kikooma (Journal of Behavioral Studies in Business, 2012)
The burden of casualty emergency handling in developing countries is enormous, challenging, and steadily increasing. There is an increasing pressure for health services to address major issues connected with management of emergencies at casualty centers. Early and effective treatment of patients could lead to substantial reduction in hospital costs, mortality, and disability (Sethi et al, 1995). However, the casualty emergency centers in many hospitals in the country are approaching “casualty status”, with poor operating climate, limited and disorganized services and facilities. The current study examined the perceived organizational internal environment, role clarity, employee empowerment, commitment, and their impact on organizational citizenship behavior (OCB) at casualty emergency centers in public and private hospitals in Uganda. The study employed a cross sectional survey design. The target population (540) comprised of casualty emergency employees. A sample size of 120 respondents from two hospitals (public X and private Y hospitals) was used and included employees from surgical unit (52.5%), Medical unit (27.5%), Intensive care unit (15.8%), Investigation unit (3.3%), and records (0.8%). A stratified random sampling design based on categories of doctors, nurses, paramedicals, and support staff was used to select the sample. Data was analyzed using SPSS package, to establish Pearson’s correlation coefficient, t-test, and regression analysis level of significance between variables and groups.
Keywords: Emergency; Role clarity; Empowerment; Commitment; Internal environment